2011
DOI: 10.1089/eco.2011.0033
|View full text |Cite
|
Sign up to set email alerts
|

What? The Earth is Sick? Undergraduate Student Awareness of Environmental Problems: A Qualitative Study

Abstract: A great deal of information about potential catastrophic global change has emerged through multiple media sources in the past several years, yet little change has been forthcoming from the populace at large. To assess penetration and effect of this information, an inductive qualitative study was performed. Nineteen college-aged men and women from a medium-sized Midwestern university participated in three interviews which asked questions relating to their awareness of global climate problems, population size, a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
5
0

Year Published

2012
2012
2019
2019

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 32 publications
1
5
0
Order By: Relevance
“…-Lake et al (2010) note that US adolescents see that responsibility for environmental problems rest with government rather than individuals; views consistent with those expressed by the cohorts in this study (see Table 10). Agreement with collective and societal environmental stewardship rather than individual action is also consistent with previous studies, e.g., Schuetz et al (2011). Statements 10.2 and 10.3 and 10.2 and 10.4 are, perhaps unsurprisingly, highly correlated (.524 and .571 respectively) as are statements 10.3 and 10.4 (.642).…”
Section: Interest and Normssupporting
confidence: 90%
See 1 more Smart Citation
“…-Lake et al (2010) note that US adolescents see that responsibility for environmental problems rest with government rather than individuals; views consistent with those expressed by the cohorts in this study (see Table 10). Agreement with collective and societal environmental stewardship rather than individual action is also consistent with previous studies, e.g., Schuetz et al (2011). Statements 10.2 and 10.3 and 10.2 and 10.4 are, perhaps unsurprisingly, highly correlated (.524 and .571 respectively) as are statements 10.3 and 10.4 (.642).…”
Section: Interest and Normssupporting
confidence: 90%
“…Of interest in the data is the stronger agreement of the Townsville cohort with ozone depletion rather than CO 2 as the cause of the greenhouse effect. Schuetz et al, 2011), and, as shown in Table 5, likely to be motivated more by financial savings than environmental concerns (Lorenzoni et al, 2007). The only high correlation (.659) in this set of statements is, unsurprisingly, between items 5.6 and 5.7.…”
Section: Knowledge (Correct or Incorrect)mentioning
confidence: 72%
“…Water issue opinions have been extensively studied by using surveys at the adult citizen level but are less known for university students. Twelve survey studies of college students about environmental issues have been published in the last 50 years (Thompson and Gasteiger, 1985; Schuetz et al, 2011). A recent survey study of university students in Lithuania, Finland, and Sweden found that college students felt a lack of clean water was the most serious environmental issue in the world (Keinonen et al, 2016).…”
mentioning
confidence: 99%
“…A lack of anticipation of benefits derived from urban nature might be cause for alarm, particularly if there is indeed a legitimate displacement of nature-based contact via the omnipresent screen. Although the erosion of our connection to nature may be obscuring its perceived benefits, and research does show that young adults in university settings continue to have minimal awareness of and concern about global climate change and other environmental issues [ 95 ], there is reason for optimism - critically, the researchers also showed that walking in nature lifted mood, and mood elevation via nature exposure appears to increase relatedness to nature. The researchers refer to this as a happy path to sustainability, a cycle that can be maintained by fostering awareness that nature has the potential to influence mood [ 94 ].…”
Section: Nature Urban Growth and Environmental Implicationsmentioning
confidence: 99%